2002
DOI: 10.1073/pnas.222546799
|View full text |Cite
|
Sign up to set email alerts
|

The identification of vesicular glutamate transporter 3 suggests novel modes of signaling by glutamate

Abstract: Quantal release of the principal excitatory neurotransmitter glutamate requires a mechanism for its transport into secretory vesicles. Within the brain, the complementary expression of vesicular glutamate transporters (VGLUTs) 1 and 2 accounts for the release of glutamate by all known excitatory neurons. We now report the identification of VGLUT3 and its expression by many cells generally considered to release a classical transmitter with properties very different from glutamate. Remarkably, subpopulations of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

68
650
0
4

Year Published

2005
2005
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 512 publications
(724 citation statements)
references
References 45 publications
68
650
0
4
Order By: Relevance
“…In the basal forebrain, axonal co-expression of VGLUT3-immunoreactivity was shown for the striatal cholinergic interneurons. In contrast, the VGLUT3-ir fibrous structures in the LS did not co-express acetylcholine, serotonin and, only rarely, GABA (Fremeau et al, 2002;Gras et al, 2002;Herzog et al, 2004).…”
Section: Introductionmentioning
confidence: 72%
“…In the basal forebrain, axonal co-expression of VGLUT3-immunoreactivity was shown for the striatal cholinergic interneurons. In contrast, the VGLUT3-ir fibrous structures in the LS did not co-express acetylcholine, serotonin and, only rarely, GABA (Fremeau et al, 2002;Gras et al, 2002;Herzog et al, 2004).…”
Section: Introductionmentioning
confidence: 72%
“…VGLUT3 is considered to be a marker for neurons that contain glutamate (Fremeau et al, 2002;Gritti et al, 2006;Guo et al, 2005). In this respect, Gritti et al have shown that almost all (96-100%) VGLUT3-labeled neurons are positively stained for phosphate-activated glutaminase (pGlu), an enzyme that synthesizes glutamate from glutamine, and that approximately 70% of pGlucontaining neurons are co-labeled with VGLUT3.…”
Section: Discussionmentioning
confidence: 99%
“…Triple-fluorescent immunohistochemical labels for c-Fos, glutamate, and β-endorphin-Currently, vesicular glutamate transporter 3 (VGLUT3), present in perikarya as well as neuronal processes, has been employed to identify neurons that use glutamate as a neurotransmitter (Fremeau et al, 2002;Gritti et al, 2006;Guo et al, 2005). Thus, we stained VGLUT3 to detect glutamatergic neurons.…”
Section: 34mentioning
confidence: 99%
“…VGLUTs accumulate glutamate in synaptic vesicles and are prime markers for excitatory glutamatergic terminals (Fremeau et al 2002(Fremeau et al , 2001Gabellec et al 2007;Kaneko et al 2002;Zhou et al 2007). In addition, we conducted retrograde tract tracing experiments combined with immunohistochemical identification of glycine and GABA to identify which CN-commissural neurons were not inhibitory.…”
Section: Introductionmentioning
confidence: 99%